Medical student perception of force application: An accuracy assessment and pilot training program - Heather Becker; Riley Duncan; D’Angeleau Newsome; Kenneth A. Zaremski; Bryan G. Beutel (Journal of Education and Health Promotion, 2024)
BACKGROUND: It is unclear how accurately students can reproduce specific forces that are often required for physical examination maneuvers. This study aimed to determine the baseline accuracy of force application for preclinical medical students, evaluate the effectiveness of a quantitative visual feedback intervention, and investigate whether certain demographics influence accuracy. MATERIALS AND METHODS: First- and second-year medical students were enrolled and demographic data were collected. Students blindly applied their estimation of 15 lbs (6.8 kg), 3 lbs (1.4 kg), 10 lbs (4.5 kg), 1.5 lbs (0.7 kg), and 6 lbs (2.7 kg) of force on a scale. Visual feedback training was then performed wherein students applied a series of additional forces unblinded five times, and then blindly administered the same five initial forces 12 minutes and one week later. Accuracy was compared at each time point and a regression analysis was evaluated for predictors of accuracy. RESULTS: Thirty-three students participated. The mean baseline accuracy was 38.3%, 41.1% immediately following intervention, and 35.6% one week later (P = 0.66). Accuracy was significantly higher at higher intended forces compared to lower forces (P < 0.05). The number of prior occupations was a positive independent predictor (P = 0.04), and the number of sports played was noted to be a negative predictor (P = 0.01), of baseline accuracy. CONCLUSIONS: Medical students’ ability to accurately reproduce clinically relevant forces is poor. There is a clear need to implement a robust training program in medical education, and students may need multiple training sessions to refine this skill.